Answer:
(x, y) = (-2, -4)
Explanation:
I like to start by putting the equations into standard form. That requires removing any common factors and making the leading coefficient positive.
-2x +2y = -4 ⇒ x -y = 2 . . . . . . divide by -2
3x +3y = -18 ⇒ x +y = -6 . . . . . divide by 3
__
Now, we can add these two equations to eliminate y:
(x -y) +(x +y) = (2) +(-6)
2x = -4 . . . . simplify
x = -2 . . . . . divide by 2
Substituting into the second equation gives ...
-2 +y = -6
y = -4 . . . . . add 2
The solution to the system of equations is (x, y) = (-2, -4).